Design of a CBN composite abrasive to improve the performance of HSG rail maintenance grinding wheel. (14th February 2022) - Liu, Peng-zhan; Yao, Yu; Zou, Wen-jun; Peng, Jin; Song, Xu-dong; Xiao, Fu-ren
Graphical abstract: Highlights: A technology for optimizing rail high-speed grinding (HSG) grinding wheel. A composite abrasive design is proposed with a porous surface and compact interior. Improve the grinding efficiency and quality of rails by composite grinding wheels. Application of CBN super-hard abrasive in rail heavy-load grinding wheel. The wear mechanisms of zirconia alumina and CBN composite abrasive are discussed. Abstract: A heavy-load resin grinding wheel with zirconia alumina abrasives plays a vital role in rail high-speed grinding (HSG) maintenance. However, the grinding wheel has the defect of short service life. Abrasives are the central performers in the cutting behavior of grinding wheels. A cubic boron nitride (CBN) composite abrasive was developed to enhance the performance of grinding wheels. The results showed composite abrasives bonded more tightly with the resin matrix, strengthening the structure of the wheel. The grinding efficiency and ratio of the composite grinding wheel were improved by 99.8% and 102% respectively, and the rail morphology was optimized.